Development and Feasibility Exploration of a Combined Compensatory and Restorative Approach to Addressing Cognitive Challenges in Early Intervention Psychosis. Issue 4 (November 2020) - Williams, Raquel S.; Virdee, Gursharan K.; Bowie, Christopher R.; Velligan, Dawn I.; Maples, Natalie J.; Herman, Yarissa; Kidd, Sean A.
Abstract: The integration of compensatory and restorative cognitive interventions is an emerging area of research and practice. However, little research has been conducted in this area, with a lack of attention given to describing the process taken to integrate the two approaches in a way that is feasible and effective. In this paper, we describe the rigorous process undertaken to integrate and develop Combined Cognitive Intervention (CCI) for early psychosis. This home-based intervention was developed within the context of a larger study comparing the effectiveness of remedial and restorative approaches in which 11 patients were randomized to receive CCI, completed evaluations at baseline, 4 months and 5 months post-intervention. Outcome analyses suggested less favorable functional outcomes for CCI but comparable gains in goal attainment and symptom reduction as those observed in other treatment conditions. Qualitative feedback on challenges and successes as experienced by participants and clinicians are provided, along with a case study to illustrate the implementation of CCI. Findings are discussed within the broader context of evidence-based interventions and the provision of services to those experiencing early psychosis. Highlights: Integrating compensatory and restorative interventions is feasible in early psychosis Participants viewed the combined intervention as helpful and acceptable An integrated approach supported individuals with achieving their recovery goals